Workplace built environment: underpinning the incentive structure for k-workers in the public sector / Siti Korota Aini Hj. Omar and Rugayah Hj. Hashim - Omar, Siti Korota Aini; Hashim, Rugayah (Research Management Institute (RMI), 2011)
This study is about the psychological attachments of human being with the workplace. It seeks to determine the relevance of workplace environment to the workers as their tangible incentives. The super-ordinate goals, in which real stakeholders (workers and the society) win, would be achievable if they are not taken for granted, but recognized as sovereign people, living in sovereign state. Reinventing a governing concept to overlap existing workable culture without consideration of the psychological need of the stakeholders is a waste of resources. Today, the market forces, which aspires to enhance state-business collaboration has re-enforced an alarming growth of elitist individuals among the decision-makers. On top of the demand for efficiency, the k-workers have to grapple with a dangerous infiltration of monopolistic corporate bodies represented by the business élites masquerading as interest groups as well as the power élites propagating their own ideology. It would be an economic catastrophe if those running the government support these minorities.